KEARIFAN LOKAL TINGKEPAN: KAJIAN PENDIDIKAN ANAK DALAM ISLAM - Rifai, Moch; Hartuti, Hartuti (Premiere Educandum, 2012)
Children are not only endearment but also the determinant for afterlife happiness. In addition, they are successors of the former generation, a familyâs pride and evidence when humans are on the judgement day of yaumulmakhsyar. Such claims are available on holly scriptures including Al Quran. Since children are so highly valued, every single mother hopes to raise excellent children. In such perspective, pregnancy and child birth become among life cycles most paid attention to. A ritual for such event, tingkepan, is therefore, usually very well arranged to do. Parents, however, are advised to be well informed about the ritual to find bless rather than sins. They are to select values good for themselves as well as for their young such as through prayers in accordance with Islamic teaching and Javanese local wisdom. Both, Islamic teaching and Javanese local wisdom have been the worldview of Javanese ancestors who are faithful to Lord God.Key words: Tingkepan, Culture, Islam